ChemInform Abstract: A Novel Base‐Promoted Cyclization: Synthesis of Substituted Benzo[b]furans. Issue 11 (8th March 2013) - Damera, Krishna; Ke, Bowen; Wang, Ke; Dai, Chaofeng; Wang, Lifang; Wang, Binghe
Abstract The method can be applied to a broad spectrum of phenols bearing alkyne chains in ortho‐position to produce highly functionalized benzofuran structures.